Adolescents' inhibitory control: keep it cool or lose control. Issue 1 (23rd November 2016) - Aïte, Ania; Cassotti, Mathieu; Linzarini, Adriano; Osmont, Anaïs; Houdé, Olivier; Borst, Grégoire
Abstract: Inhibitory control (i.e., the ability to resist automatisms, temptations, distractions, or interference and to adapt to conflicting situations) is a determinant of cognitive and socio‐emotional development. In light of the discrepancies of previous findings on the development of inhibitory control in affectively charged contexts, two important issues need to be addressed. We need to determine (a) whether cool inhibitory control (in affectively neutral contexts) and hot inhibitory control (in affectively charged contexts) follow the same developmental pattern and (b) the degree of specificity of these two types of inhibitory control at different ages. Thus, in the present study, we investigated the developmental patterns of cool and hot inhibitory control and the degree of specificity of these abilities in children, adolescents and adults. Typically developing children, adolescents, and adults performed two Stroop ‐like tasks: an affectively neutral one ( Cool Stroop task) and an affectively charged one ( Hot Stroop task). In the Cool Stroop task, the participants were asked to identify the ink color of the words independent of color that the words named; in the Hot Stroop task, the participants were asked to identify the emotional expression of a face independent of the emotion named by a simultaneously displayed written word. We found that cool inhibitory control abilities develop linearly with age, whereas hot inhibitory control abilities follow a quadratic developmental pattern, with adolescents displaying worse hot inhibitory control abilities than children and adults. In addition, cool and hot inhibitory control abilities were correlated in children but not in adolescents and adults. The present study suggests (a) that cool and hot inhibitory control abilities develop differently from childhood to adulthood – i.e., that cool inhibition follows a linear developmental pattern and hot inhibition follows an adolescent‐specific pattern – and (b) that they become progressively more domain‐specific with age. Abstract : The present study suggests (a) that cool and hot inhibitory control abilities develop differently from childhood to adulthood – with a linear developmental pattern but an adolescent‐specific one for cool and hot inhibitory control abilities, respectively – and (b) that they progressively become more domain‐specific with age.